“We Were as Dreamers:” Prayer as the Royal Road to the Unconscious in Hasidism - Moseson, Elly (Numen, 2022)
This study explores the Hasidic psychologization of Jewish mysticism by focusing on the problem of distracting thoughts that arise during prayer, and the attitudes and responses to them that can be found in Hasidic literature. Two different theories of the origins of such thoughts, both attributed to Israel Ba’al Shem Tov, along with various techniques for engaging with them, are described. It is argued that these theories reflect two distinct paradigms, both of which exhibit significant similarities to the dynamic unconscious of psychoanalysis. In addition to tracing the reception of Israel’s ideas on distracting thoughts within the Hasidic movement and without, the study connects them to his activities as a folk healer with a particular concern with treating mental illness.